The domestic space in the architecture of fernando martínez sanabria. the wall as a spatial integrator (2010)
This study is about a formal process of transformation in six houses that Fernando Martinez Sanabria produced in Bogota between 1957 and 1963 during modern architecture, in which a specific conception of domestic space is proposed. The study provides a formal analysis on the order, elements, and strategies of spatial delimitation of the social areas, from these projects and built works, as well as other Martinez Sanabria’s works and others architects. The results indicate the recovery of the relationship of the house into the interior, through a form of a spatial integration from the wall, which concentrates and vitalize the interior space, renewing the validity of values like intimacy, privacy, and seclusion, considered essential to the domestic.